An Analysis of Integrated Practicum Demands of Virtual Lab Models in Hydrocarbon Materials - Erlina Erlina (Budapest International Research and Critics University, 2018)
This study aims to determine the effect of the implementation of a practical guide to interact with a virtual laboratory model on students' understanding of practicing on hydrocarbon materials. Students' understanding is included in the dimensions of cognitive and affective processes. This research was conducted at the Percut Sei Tuan Pure Pure Private High School in the odd semester of the 2018/2019 school year. The research method used was quasi experimental design with pretest-posttest control group design. Sampling was done using purposive sampling technique. The sample in the study were students of class XI MIA 2 as an experimental group with learning using virtual laboratories and students of class XI MIA 1 as a control group using conventional learning. The sample in each group amounted to 36 people. Data retrieval is done using a description of students' concept understanding. Data analysis using independent sample T-Test test obtained t count of 3.021 with t table 2.045 means that t count> t table and significant value 0.004 <0.05. Then Ho is rejected and H1 is accepted at a significant level of 0.05 so it is concluded that there is a significant difference between the average posttest value of the experimental group and the control group. This shows that there is an effect of applying virtual laboratories to students' concept understanding.